Sistem Pakar Menggunakan Metode Case Based Reasoning dalam Akurasi Penyakit Disebabkan oleh Bakteri Staphylococcus Aureus - Surya Aulia Rahman; S Sumijan (Jurnal Sistim Informasi dan Teknologi, 2021)
Staphylococcus aureus is the most worrisome bacteria in the world of health because it is highly pathogenic and can cause serious infections in previously healthy individuals. Staphylococcus aureus has gram-positive cells, round (cocci) 0.7-0.9 µm in diameter, non-spore-forming, non-motile, facultative anoerobes, in colony shaped like a grape string. This bacterial infection in humans varies in severity, from minor skin infections (furunculosis and impertigo), urinary tract infections, respiratory infections, to eye infections. This causes many patients to need an expert (doctor) to consult about the symptoms that a patient appears or experiences and the risk factors felt by the patient. So they conducted this research using the Case Based Reasoning (CBR) method which consists of 4 steps, namely retrieve, reuse, retain and revise. By using the case-based reasoning method for a problem with the staphylococcus aureus bacterial disease, it is easier for a patient to find treatment and a solution. With an expert system using this method (case based reasoning), experts (doctors) can easily find out what diseases are suffered by staphylococcus. That way, patients with staphylococcus disease are prepared to deal with the disease they are suffering from.